Excessive Subchorionic Fibrinoid Deposition as a Component of Massive Perivillous Fibrin Deposition: A Case With Maternal Immune Thrombocytopenia. (July 2022) - Taweevisit, Mana; Nimitpanya, Panachai; Thorner, Paul S.
Maternal floor infarction (MFI) and massive perivillous fibrin deposition (MPFD) are overlapping placental disorders of unknown etiology, associated with adverse obstetric outcome, and a significant risk of recurrence. We describe a 31-year-old mother with asymptomatic thrombocytopenia throughout pregnancy and a positive lupus anticoagulant. She delivered a normal female neonate at term, whose weight was small for gestational age, with a placenta weighing less than the 10 th percentile. Placental examination showed MPFD together with excessive subchorionic fibrinoid deposition. The placenta showed diffuse C4d deposition and an immune-mediated reaction was postulated for the pathogenesis of the placental changes. We suggest that excessive subchorionic fibrinoid deposition may be part of the morphologic spectrum of MFI/MPFD.